New records of Dolichopodidae (Diptera) from Mordovia, Russia - I.Ya. Grichanov (Russian Academy of Science. Southern Scientific Centre. Federal Research Centre, 2021)
A new material of Dolichopodidae has been recently collected and identified, and includes 72 species (39 species are new for the Republic of Mordovia, 60 species have been found for the first time in the Mordovian Nature Reserve and its environs, and one species is new for the Smolny National Park). In total, 98 species are recorded in this region that apparently makes up 40–50% of actual Dolichopodidae fauna in the Republic of Mordovia. This paper provides also distribution pattern for each collected species. The list of species found in the Mordovian Nature Reserve has increased from 11 to 71.